PERILAKU KONSUMSI PEMAKAIAN KAWAT GIGI NON MEDIS (Study Tentang Pemakai Kawat Gigi Non Medis di Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi) - Sulmayeti "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study titled consumption behavior of non-medical use of braces ( the study of non medical users of braces in the sub kuantan mudik kuantan singingi). This study aims to determine the caracteristics of the social, economic, non medical users of braces. There is also an explanation of the background of the consumption behavior of non medical use of braces.To analyze the data descriptive qualitative research conducted is aimed at revealing the facts, phenomena, variables, and the state wich occurs when running and deliver research is in accordance facts on the ground.Socio-economic characteristic of non-medical users of braces that is composed of male gender and woman aged 14 to 28 years who have junior high school, senior high school, graduate or equivalent which is the subject of research work consisted of student, students treaders, salon workers, tailors, and the driver with income up to 280.000 ro Rp. 3.500.000. consumption behavior of non medical use of braces that income and knowledge about the low braces as well the desire to raise the self-image and raise the social status so called beautiful, cool, popular, confident, and raise the social status so called rich and more acceptable in society.Keywords : Consumption Behavior, use, non-medical braces